ANALISIS PERBANDINGAN PENERIMAAN PKB SEBELUM DAN SESUDAH PENERAPAN TARIF PROGRESIF DAN PENGARUHNYA TERHADAP PENERIMAAN BBNKB (STUDI PADA KANTOR CABANG PELAYANAN DISPENDA PROVINSI WILAYAH KOTA BANDUNG II KAWALUYAAN - Nurdin, Sahidillah; Riana, Dwiza (LPPM Universitas BSI, 2013)
ABSTRACTThis research was meant to find out motor vehicle tax revenue before and after progressive rates, whether there are differences motor vehicle tax revenue before and after the implementation of progressive rates, and influences motor vehicle tax revenue against the import duty receipts BBNKB. A method of research use is a method of comparative and descriptive analytical with the method approach case study. Analysis tool used is the t-test statistics parametris and simple regression test with scale ratio measurement. Hypothesis testing using the test average and difference test t. The research results shows that receipt of motor vehicle tax before the application of progressive rates up and down experience acceptance, motor vehicle tax revenues after the application of progressive rates are having an increasing trend on average, acceptance of progressive rates that there is a significant difference between motor vehicle tax revenues before and after the application of progressive rates, testing of the influence of motor vehicle tax revenues against the acceptance of the customs behind the name of a motor vehicle that is a motor vehicle tax revenues significantly to acceptance influential of the BBNKB Keywords : motor vehicle tax revenue, progressive rates, BBNKB of revenues.